Factors in Raising The Culture of Reading Among The Youth of Uzbekistan - Orasta Azamovna Obidova (Research Parks Publishers, 2021)
In Uzbekistan, which has a place in the world intellectual system, the focus on raising the culture of youth reading and enriching it with modern spiritual and intellectual needs and socio-cultural factors is becoming more important than ever. During the period of independence, special attention was paid to the study of our national spiritual and intellectual heritage on the basis of new thinking and its use for the strategic development of society. In this article, the author analyzes the work being done to promote the culture of reading among the youth of Uzbekistan and the factors influencing